Writing and learning - Gere, Anne Ruggles (Macmillan, 1988)
In this comprehensive, accessible guide, pre- and in-service K-12 teachers get a firm understanding of the essential topics of first and second language acquisition along with teaching and assessment strategies for oral language development, vocabulary, writing, reading, and reading and writing across the curriculum.